Ukas URGENSI PELAKSANAAN PERATURAN PEMERINTAH NO. 22 TAHUN 2021 KAITANNYA DENGAN PENGATURAN PENGELOLAAN LINGKUNGAN HIDUP DI KOTA BATAM : URGENCY FOR IMPLEMENTING GOVERNMENT REGULATION NO. 22 OF 2021 IN RELATION TO ENVIRONMENTAL MANAGEMENT ARRANGEMENTS IN BATAM CITY - Ukas, Ukas (Jurnal Cahaya Keadilan, 2024)
Environmental Law, Forms of Regulation, Management and Utilization of the environment, both based on UUPPLH in general, have specific regulations such as Government Regulation Number 22 of 2021. provide benefits and/or utilization of the environment if existing policies are fully planned. Talking about and understanding the environment will provide different insights based on the viewpoint of the environmental object itself, but it still boils down to the regulation, management and use of the environment. Environmental management means that future development needs to be planned and/or planned so that it becomes an environment that is in line with the development of the environment itself. Forms of integrated environmental management, environmental protection, environmental management objectives and creating better environmental quality. Government Regulation Number 22 of 2021, follows developments in the development of environmental insight and the dynamics of economic development and societal diversity. Hope for people's rights to enjoy a clean and healthy environment is the ultimate goal of this Government Regulation.